1992
DOI: 10.1002/j.1460-2075.1992.tb05054.x
|View full text |Cite
|
Sign up to set email alerts
|

CpG methylated minichromosomes become inaccessible for V(D)J recombination after undergoing replication.

Abstract: The physical parameters controlling the accessibility of antigen receptor loci to the V(D)J recombination activity are unknown. We have used minichromosome substrates to study the role that CpG methylation might play in controlling V(D)J recombination site accessibility. We find that CpG methylation decreases the V(D)J recombination of these substrates more than 100‐fold. The decrease correlates with a considerable increase in resistance to endonuclease digestion of the methylated minichromosome DNA. The minic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
3

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(90 citation statements)
references
References 50 publications
3
84
0
3
Order By: Relevance
“…Methylation also may serve a negative role by repressing the basal level of recombination throughout the loci and cryptic genomic sites. Previous studies have demonstrated that methylated recombination substrates are less recombinationally active (15)(16)(17). Further studies are required to isolate the factors that confer specificity to the recombination process and to determine the mechanism by which they alter the accessibility of loci for recombination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylation also may serve a negative role by repressing the basal level of recombination throughout the loci and cryptic genomic sites. Previous studies have demonstrated that methylated recombination substrates are less recombinationally active (15)(16)(17). Further studies are required to isolate the factors that confer specificity to the recombination process and to determine the mechanism by which they alter the accessibility of loci for recombination.…”
Section: Discussionmentioning
confidence: 99%
“…Regulated demethylation could control the specificity of the V(D)J recombinase. Consistent with such a concept, exogenously introduced hypermethylated recombination substrates including both episomes and transgenes are refractory to V(D)J recombination compared with their unmethylated counterparts (15)(16)(17). At a minimum, this suggests that methylation of target sites bound by ubiquitous trans-acting factors inhibits recombination so that demethylation of these loci should be required for the initiation of recombination.…”
mentioning
confidence: 84%
“…The most direct evidence that DNA methylation suppresses homologous recombination has come from the work in Ascobolus, but several studies support a similar role in mammalian cells. For example, V(D)J recombination is reduced more than 100-fold when the recombination substrate is methylated (Hsieh and Lieber, 1992). In addition, Dnmt1 knockout ES cells exhibit a 10-fold increased mutation rate involving gene rearrangements (Chen et al, 1998), and individuals with ICF syndrome or cultured cells treated with 5-azaCdR show increased numbers of chromosomal translocations (Ji et al, 1997;Miniou et al, 1994).…”
Section: Dna Hypomethylation ± Roles In Cancer and Genome Stabilitymentioning
confidence: 99%
“…Recombination of these inappropriately broken ends might be responsible for the chromosomal translocations common to lymphoid leukemias and lymphomas (Korsmeyer 1992;Gauss and Lieber 1993) We infer that mechanisms, in addition to heptamer-nonamer recognition, must exist to limit the error rate of the V(D)J recombinase. Some data suggest that one such mechanism involves DNA methylation (Hsieh and Lieber 1992). Another mechanism might involve transcription activity.…”
Section: The Structure Of Broken-ended Rss Dna a Probable V{d)j Recomentioning
confidence: 99%